Implementation of Hypertension Exercises to Lower Blood Pressure in Elderly People with Hypertension in Ikedaen Okinawa Japan - Fatikha, Jihan Natasya; Jati, Riani Pradara (Global Health Science Group, 2024)
Hypertension is often referred to as the